2020
DOI: 10.7441/joc.2020.02.01
|View full text |Cite
|
Sign up to set email alerts
|

The Scope of an Integrated Analysis of Trust Switching Barriers, Customer Satisfaction and Loyalty

Abstract: This study investigated the impact of service quality, intimacy, trust, and playfulness on customer loyalty. The integrated variables were investigated alongside their effect on customer loyalty. Variance-based structural equation modeling with PLS (PLS-SEM) was selected to assess the proposed hypotheses, with the analysis sample of the study including 627 questionnaires distributed to the sampled subjects. The positive effect of service quality, playfulness, intimacy, trust, and satisfaction was found, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
2
24
0
1
Order By: Relevance
“…Trust in a trading relationship is an asset that creates benefit (Bencsik et al, 2020;Gorb, 2017;Masuku & Kirsten, 2004;Tarí et al, 2020). On the other hand, trust helps in reducing performance uncertainty and plays a vital role in a relational transaction (Alkhurshan & Rjoub, 2020;Li & Nicholls, 2000). For this reasons creation of the relationship based on a trust and mutual responsibility becomes important component of the current supply chain management (Kot et al, 2020;Vo et al, 2020) as well as internal management systems (Bilan et al, 2020).…”
Section: Relationship Qualitymentioning
confidence: 99%
“…Trust in a trading relationship is an asset that creates benefit (Bencsik et al, 2020;Gorb, 2017;Masuku & Kirsten, 2004;Tarí et al, 2020). On the other hand, trust helps in reducing performance uncertainty and plays a vital role in a relational transaction (Alkhurshan & Rjoub, 2020;Li & Nicholls, 2000). For this reasons creation of the relationship based on a trust and mutual responsibility becomes important component of the current supply chain management (Kot et al, 2020;Vo et al, 2020) as well as internal management systems (Bilan et al, 2020).…”
Section: Relationship Qualitymentioning
confidence: 99%
“…Customer trust is a determining factor for the continuity of buyer relationships (Rampl et al 2012). Alkhurshan et al (2020) The positive effects of trust, service quality, pleasure, intimacy and satisfaction have a positive and statistically significant impact on customer loyalty. Kennedy et al (2019) states that positive results throughout the organization are carried out by monitoring service standards, this shows the positive impact of services on performance.…”
Section: Demographicmentioning
confidence: 99%
“…Food and related products were categorized as factors with low levels of engagement/participation (Beharrell & Denison, 1995). However, this perspective has drastically changed in recent years with vast improvements in agriculture, welfare, animal care, and overall health, which has made food-related activities a matter of interest, especially in tourism and marketing contexts (Alkhurshan & Rjoub, 2020;Wu & Ai, 2016). While early studies have suggested that those, deeply and thoroughly involved with food are more comfortable to distinguish and treat foods differently (Bell & Marshall, 2003;Chen, 2007), recent studies have pinpointed other aspects such as authenticity, sustainability (Zhang et al, 2019), trust, satisfaction, loyalty, and switching barriers (i.e., Alkhurshan & Rjoub, 2020;Dawi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Budianto (2019) it was noted that satisfaction and loyalty have correlations that are statistically positive. Switching barriers are known as elements influential on retaining customers and their satisfaction (Alkhurshan & Rjoub, 2020). Studies have reported a linkage between satisfaction and loyalty on an extensive manner.…”
Section: Introductionmentioning
confidence: 99%